Evaluation of surface water availability for inland valleys rice production: the case of Mankran Watershed in a deciduous forest zone of Ghana - Dawuni, B.N.; Namara, Regassa E.; Kizito, Fred; Fujii, H. (2012)
In Ghana, inland valleys have been found to be suitable for rice cultivation and could potentially increase lowland paddy rice production. This study estimated the temporal variations of surface water resources and their spatial distribution in the Mankran watershed of Ghana through the collection of recorded hydrological data in the bench mark watershedfrom2008 to 2010. Since most inland valley rice cultivation highly depends on rainfall, the watershed precipitation data over a decadal period showed sufficient wet years with a potential to sustain a high cultivation of paddy rice. Peak wetness occurred in June and October over a bi-modal precipitation pattern. Rating curve data for the Mankran-kesse river-upstream depicted low discharge values despite having a higher stream order. Thus stream order alone was not sufficient to estimate water resources potential. It was presumed that the geomorphology and lithology of the highly porous river bed and the presence of high sub-surface water resources stored in this zone may be implicated for this observation. Provision of water storage options for zones like Kesse-upstream seems a feasible option in order to cater for supplementary irrigation while indirectly tapping on subsurface water resources stored in the porous aquifers through basin interflows. Base flow data also showed that the discharge from upstream locations to the downstream exit of the watershed was high through direct surface river discharge and subsurface interflow. The temporal patterns of the hydrology indicate that annual paddy rice cultivation is ideal between May and October.